The growth pattern of sea cucumber Acaudina sp. from the Delta Wulan, Demak, Central Java, Indonesia. Issue 1 (February 2021) - Widianingsih, W; Hartati, R; Nuraeni, R A T; Endrawati, H; Mahendrajaya, R T
Abstract: Sea cucumber Acaudina sp. is one of the many benthic organisms found in the Wulan Delta ecosystem, Demak. Acaudina sp. plays an important role in the benthic ecosystem. Therefore, a study on the population of Acaudina sp. is necessary. The purpose of this study was to determine the growth pattern of sea cucumber Acaudina sp. Sea cucumber samples were taken in May, June, and July 2020 during the new moon and full moon phase. Based on the statistical test, it was found that there is no significant different the mean of total weight (gram) between new moon and full moon (t-test two paired; df = 2; t count = -1.481; P=0.05). Likewise, there is no different in the average value of sea cucumber length in the full moon and new moon phases (t-test two paired; df = 2; t count = 0.353; P=0.05). The average of total weight value of Acaudina sp. on full moon had range 15.21–27.5 gram, is lower than on new moon (20.47–32.11 gram).The growth pattern of sea cucumber Acaudina sp. on full moon and new moon are negative allometric.